Communication for peace as a social transformation tool - Espinoza Bonifaz, Augusto Renzo (2017)
This article proposes to use the concept of communication for peace as a tool to improve the quality of information disseminated by the media. Firstly, it seeks to build a definition of communication for peace, and establish the minimum standards that this type of social communication matters. Then, it is intended to establish certain criteria to identify their presence in the media, and propose reforms in the respective public policies, but not before performing an analysis using statistics on the current situation of our radio and television.